A thermodynamically consistent model of finite-state machines. Issue 6 (6th December 2018) - Chu, Dominique; Spinney, Richard E.
Abstract : Finite-state machines (FSMs) are a theoretically and practically important model of computation. We propose a general, thermodynamically consistent model of FSMs and characterize the resource requirements of these machines. We model FSMs as time-inhomogeneous Markov chains. The computation is driven by instantaneous manipulations of the energy levels of the states. We calculate the entropy production of the machine, its error probability, and the time required to complete one update step. We find that a sequence of generalized bit-setting operations is sufficient to implement any FSM.